(untitled) (Revista de Ciências Agroveterinárias, 2023)
Through this work, the pharmacokinetics of Norfloxacin in pigeons were explored by using six healthy male pigeons as the subjects for this study. The pharmacokinetic indices of orally administered Norfloxacin were obtained by microbiological assay and then the data were fitted to the two-compartment pharmacokinetic open model to evaluate the distribution and excretion parameters. In the achieved results, the calculated absorption rate constant (Kab) was 1.26 h-1, the maximum achieved concentration of Norfloxacin was 2.75 μg/ml at 1.34 hr., the volume of distribution (Vd/F) was 3.15 L/kg. The half-life (t1/2β) was 4.9 hrs., the calculated area under the curve of Norfloxacin (AUC0-t) was 16.75 (h*μg)/ml, while the clearance of Norfloxacin (Cl/F) was 0.49 L/hr/kg. In conclusion, the pharmacokinetic parameters of Norfloxacin in pigeons are not far away from other birds like chickens, considering the differences among them. Norfloxacin is a valuable antibacterial agent against susceptible bacterial infections depending on the obtained pharmacokinetic profile. In conclusion, pharmacokinetic parameters of Norfloxacin in pigeons are not far away from other birds like chicken considering the differences in species, moreover Norfloxacin is a valuable antibacterial agent against susceptible bacterial infections depending on the obtained pharmacokinetic profile.